2005
DOI: 10.1166/jnn.2005.180
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Nucleation and Growth of Single Wall Carbon Nanotubes via the HiPco Process: A Catalyst Concentration Study

Abstract: Using the High Pressure carbon monoxide (HiPco) reactor we conducted an experiment on the effects of changing the catalyst concentration. With each catalyst concentration tested the resulting raw HiPco material was characterized for average SWNT lengths, SWNT diameters, residual iron particle size, and large fullerene content. We were able to determine trends in each of these characteristics as the catalyst concentration was changed. As the catalyst concentration was decreased SWNT lengths increased, SWNT diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 0 publications
1
27
1
Order By: Relevance
“…[22] HiPco was the first process that allowed the production of gram-scale quantities of SWNTs, and triggered an explosion of studies on various SWNTs. [23] Even today, many research groups utilize the HiPco process to produce starting materials for various CNT applications. [23] Even today, many research groups utilize the HiPco process to produce starting materials for various CNT applications.…”
Section: Gas-phase Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] HiPco was the first process that allowed the production of gram-scale quantities of SWNTs, and triggered an explosion of studies on various SWNTs. [23] Even today, many research groups utilize the HiPco process to produce starting materials for various CNT applications. [23] Even today, many research groups utilize the HiPco process to produce starting materials for various CNT applications.…”
Section: Gas-phase Growthmentioning
confidence: 99%
“…[23] Even today, many research groups utilize the HiPco process to produce starting materials for various CNT applications. [23] Heating decomposes Fe(CO) 5 into Fe(CO) n , where n = (0-4), produces Fe atoms condensed into clusters. What is more, the HiPco process can be said to be the forebear of the other SWNT production processes, for its remarkable influence on the subsequently developed methodologies of not only for the electrode applications but also for the purely semiconducting SWNT productions.…”
Section: Gas-phase Growthmentioning
confidence: 99%
“…This study uses a log‐normal distribution, previously found to closely represent AFM distributions of produced SWCNTs . The log‐normal distribution is defined by two parameters, the average µ and standard deviation σ of ln( L ).…”
Section: Theorymentioning
confidence: 99%
“…Due to their cost-effectiveness, the commercial use of CNF has grown exponentially [3,4]. CNT and CNF are elongated structures with a high aspect ratio (up to 1:1000, length/width) produced predominantly by HiPco, chemical vapor deposition, laser ablation or arc discharge by employing a variety of catalytic metal particles [5]. The purity of CNT and CNF depends on the technology used and on the subsequently applied purification procedures.…”
Section: Introductionmentioning
confidence: 99%